Team‐external coordination in large‐scale software development projects. Issue 3 (28th June 2020) - Sablis, Aivars; Smite, Darja; Moe, Nils
Abstract: High‐quality work is said to depend on team abilities. However, teams working in large‐scale projects often do not have all expertise to complete their tasks, which are also highly interdependent. Therefore, teams need to rely on coordination with other teams, experts, and supporting roles. In this paper, we explore teams' coordination needs and evaluate the impact of the satisfaction of these needs on team performance. We conducted an embedded multicase study with nine teams in two projects in two companies. We collected qualitative data through nine focus groups and 19 interviews and quantitative data using a questionnaire with 49 members from the studied teams. Our results suggest that project‐, team‐, and task‐related characteristics impact teams' coordination needs. Even in the same project, teams may have different expertise and work coordination needs. We found that the satisfaction of these needs seems to influence teams' performance, although our results are inconclusive and yield a closer look in future research. On the basis of our findings, we recommend the companies to cultivate a networking culture and support teams external coordination with other teams and experts, paying attention to their needs, for example, driven by a lack of experience or increased work complexity. Abstract : High‐quality work is said to depend on team abilities. However, teams working in large‐scale projects often do not have all expertise to complete their tasks, which are also highly interdependent. In this paper, we explore teams' coordination needs and how teams rely on coordination with other teams, experts, and supporting roles to address these needs.